Functional Imaging Combined with Multi-Detector CT: A Radionuclide Imaging Perspective - D. Winant, Celeste; Kim, Sangtaek; Seo, Youngho (Current Medical Imaging, 2010)
The combination of functional and anatomical information through dual-modality imaging has brought about a revolution in the diagnostic and prognostic impact of noninvasive in vivo imaging. As the current marketplace shows, one of the best means of combining anatomical and functional imaging methods is to integrate the two modalities around a common table or bed, and perform the two scans sequentially while the subject assumes the same position. This has both been technologically and clinically demonstrated with dual-modality SPECT/CT and PET/CT. We review the roles of high-quality state-of-the-art multi-detector CT (MDCT16+; 16 or greater detector rows, x-ray tube with a minimum power output of 50 kW) in dual-modality SPECT/CT and PET/CT imaging. We give a brief history of the development of SPECT/CT and PET/CT, and give an overview of commercial SPECT/MDCT16+ and PET/MDCT16+ cameras presently available for clinical applications. We next give an overview of the current and potential applications of SPECT/MDCT16+ and PET/MDCT16+, discussing clinical applications and specific innovations in image reconstruction and information management. We follow with a discussion of the clinical impact of MDCT16+ in dual-modality imaging. We compare the tradeoffs of MDCT16+ versus single- or few-detector CT as the anatomical imaging-component of the dual-mode scanner. Finally, we also briefly discuss the clinical tradeoffs in terms of workflow of separate MDCT16+ and functional (SPECT or PET) cameras versus one combined dual-modality scanner.
Keywords: SPECT